2012
DOI: 10.1103/physrevb.86.024527
|View full text |Cite
|
Sign up to set email alerts
|

Surface-induced magnetic fluctuations in a single-crystal NiBi3superconductor

Abstract: We report anistropy in superconducting and normal state of NiBi3 single crystals with Tc = 4.06 K. The magnetoresistance results indicate the absence of scattering usually associated with ferromagnetic metals, suggesting the absence of bulk long range magnetic order below 300 K. However, the electron spin resonance results demonstrate that ferromagnetism fluctuations exist on the surface of the crystal below 150K.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 28 publications
(38 reference statements)
4
37
0
1
Order By: Relevance
“…29 Critical temperature of polycrystals and in nanostructured samples is also similar. [30][31][32]38 The specific heat (Fig. 4) shows a small peak at the transition, of size expected for a weak coupling BCS superconductor, C/T c = 1.43γ if we take γ ≈ 9 mJ/K 2 mol, which is compatible to the estimated zero-temperature extrapolation of C/T .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…29 Critical temperature of polycrystals and in nanostructured samples is also similar. [30][31][32]38 The specific heat (Fig. 4) shows a small peak at the transition, of size expected for a weak coupling BCS superconductor, C/T c = 1.43γ if we take γ ≈ 9 mJ/K 2 mol, which is compatible to the estimated zero-temperature extrapolation of C/T .…”
Section: Resultssupporting
confidence: 72%
“…30 Further work shows that ferromagnetism is absent in bulk single-crystal samples below 300 K, but that some kind of fluctuations do exist below 150 K just at the surface. 31 In the same spirit, other authors remark the absence of ferromagnetic behavior in bulk single crystals, but show ferromagnetic and superconducting features in nanostructures. They highlight confinement effects which eventually modify the electronic band structure.…”
Section: Introductionmentioning
confidence: 79%
“…Such incomplete and irreproducible transitions suggest that the superconductivity is extrinsic in both cases and the anomalies in the resistivity can be attributed to minority phases. In fact, it is highly likely that the higher-temperature anomaly is related to the superconducting transition of the Ni-Bi binaries (NiBi with T c ≈ 4.25 K and NiBi 3 with T c ≈ 4.06 K) [18,19]. The lower-temperature anomaly is probably caused by filamentary, thin film, Bi presented in the sample, which is consistent with the previous work [9]; the T c of Bi film can vary from 2 K to 5 K depending on its thickness [20].…”
Section: Resistivity Of Rni 1−x Bi 2±ymentioning
confidence: 99%
“…Pineiro et al studied the possible coexistence of superconductivity and magnetism in Bi 3 Ni and showed that it presents a ferromagnetic characteristic up to 750 K, well above the Ni Curie temperature 10 11 . They demonstrated from electron spin resonance that ferromagnetic fluctuations exist on the surface of the crystal below 150 K.…”
Section: Introductionmentioning
confidence: 99%